2019
DOI: 10.1111/plb.12955
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐sequencing of Solanum commersonii small RNA libraries reveals riboregulators involved in cold stress response

Abstract: Among wild species used in potato breeding, Solanum commersonii displays the highest tolerance to low temperatures under both acclimated (ACC) and non-acclimated (NACC) conditions. It is also the first wild potato relative with a known whole genome sequence. Recent studies have shown that abiotic stresses induce changes in the expression of many small non-coding RNA (sncRNA).• We determined the small non-coding RNA (sncRNAome) of two clones of S. commersonii contrasting in their cold response phenotypes via sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Interestingly, two ScWRKYs (ScWRKY010 and ScWRKY002) carried three WDs. This might be the result of the acquisition of a WRKY domain during evolution, supporting findings of Aversano et al 15 and Esposito et al 31,55 , who reported that S. commersonii prosper lineage-specific segmental duplications during evolution. Not only WDs number, but also WDs structural divergences identified in S. commersonii and S. chacoense might be the consequence of mutations during the process of evolution.…”
Section: Structural Analysis Of Scwrkys and Schwrkys Revealed Interspsupporting
confidence: 83%
“…Interestingly, two ScWRKYs (ScWRKY010 and ScWRKY002) carried three WDs. This might be the result of the acquisition of a WRKY domain during evolution, supporting findings of Aversano et al 15 and Esposito et al 31,55 , who reported that S. commersonii prosper lineage-specific segmental duplications during evolution. Not only WDs number, but also WDs structural divergences identified in S. commersonii and S. chacoense might be the consequence of mutations during the process of evolution.…”
Section: Structural Analysis Of Scwrkys and Schwrkys Revealed Interspsupporting
confidence: 83%
“…The expression profiles of the HMG genes across four different tissues of S. commersonii and S. tuberosum (flower, leaf, root and stolon) were also studied. In particular, raw data for S. commersonii (deposited under the study SRP050412) and S. tuberosum (ERR029909, ERR029910, ERR029914 and ERR029917) were downloaded and analyzed, using Cufflinks-Cuffquant software (version 2.2.1); expression values for each gene were expressed as RPKM (Reads Per Kilobase of transcript per Million mapped reads), as described by Esposito et al [24,31,32].…”
Section: Identification Of Candidate Hmg Genes and Phylogenetic Analysismentioning
confidence: 99%
“…Since the first discovery of miRNAs, the basic understanding of how gene expression is controlled deeply changed. In the last ten years, studies demonstrated that miRNAs play crucial roles in modulating stress response, including salinity [78], drought [79], waterlogging [80], UV-B radiation and cold stress [81,82], and in several cases their biological role has been clarified. For instance, miR394 and miR397 have been reported to positively regulate cold tolerance via the CBF-dependent pathway [83,84], whereas miR319 activates the CBF regulon and triggers reactive oxygen species (ROS) elimination from the cells [85].…”
Section: Genomics and Machine Learning: A Case Study To Predict Diffementioning
confidence: 99%